Effects of operating parameters on enzymatic clarification of bambangan (Mangifera pajang) juice using pectinase - Divina, Ivy Bazar; Chew, Wen Yee; Lee, Jau Shya; Saallah, Suryani; Mohd Nor, Mohd Zuhair; Roslan, Jumardi (Hibiscus Publisher Enterprise, 2024)
Bambangan juice is known for its relatively high viscosity and cloudiness, often leading to sedimentation post-bottling. These attributes are attributed to the presence of polysaccharides like pectin and starch, which contribute to instability and degradation during storage. Clarification processes, typically involving enzymatic treatment, are essential to achieve a clear, bright juice with low viscosity. Hence, this research aims to identify the optimal operating conditions (enzyme concentration, temperature, and incubation time) for bambangan juice clarification using pectinase derived from Aspergillus aculeatus. Assessment of juice quality was based on yield and various physicochemical properties. The most effective parameters for bambangan juice clarification with pectinase were found to be an enzyme concentration of 0.10% v/v, a temperature of 40 C, and an incubation time of 30 minutes. These conditions substantially enhanced juice characteristics, including yield, clarity, and color (L*, a*, b*), with respective values of 87%, 0.5, and L*-61.1; a*-2.7; b*-1.4.